Karakteristik Fisikokimia : Pewarna Makanan Dari Ekstrak Bunga Telang (Clitoria Ternatea) Yang Kaya Anti Oksidan - Yuniar, Rizka Ayu; Hafizi, Muhammad Ridho (Program Studi Teknologi Pangan, 2024)
The butterfly pea flower can be used as a food coloring to provide color, enhance visual appeal, and maintain or improve its organoleptic properties. Its role is not only limited to aesthetic aspects, but also has a significant health impact. Antioxidants owned by telang flowers have health potential, namely as anti-microbial, anti-depressant, anthelmintic, anti-cancer, and anti-diabetes. Therefore, the purpose of this research is to produce a powdered food coloring using telang flowers as the base material, which contains anthocyanins as a high source of antioxidants. This research method includes extraction with a 1% acetic acid solvent, a solubility test, a yield test, water content, and anthocyanin content. Maltodextrin (5,10,15%) and Carboxy Methyl Cellulose (CMC) were used as good capsulants. The total anthocyanin content determination test used the UV-Vis spectrometry method. The test results showed that increasing maltodextrin concentration was directly proportional to solubility, yield, and moisture content but inversely proportional to total anthocyanin content.